Long-range transport of coarse mineral dust: an evaluation of the Met Office Unified Model against aircraft observations - N. G. Ratcliffe; C. L. Ryder; N. Bellouin; S. Woodward; A. Jones; B. Johnson; L.-M. Wieland; M. Dollner; J. Gasteiger; J. Gasteiger; B. Weinzierl (Atmospheric Chemistry and Physics)
Coarse mineral dust particles have been observed much further from the Sahara than expected based on theory. They have impacts different to finer particles on Earth's radiative budget, as well as carbon and hydrological cycles, though they tend to be under-represented in climate models. We use measurements of the full dust size distribution from aircraft campaigns over the Sahara, Canaries, Cabo Verde and Caribbean. We assess the observed and modelled dust size distribution over long-range transport at high vertical resolution using the Met Office Unified Model, which represents dust up to 63.2 µm diameter, greater than most climate models. We show that the model generally replicates the vertical distribution of the total dust mass but transports larger dust particles too low in the atmosphere. Importantly, coarse particles in the model are deposited too quickly, resulting in an underestimation of dust mass that is exacerbated with westwards transport; the 20–63 µm dust mass contribution between 2 and 3.7 km altitude is underestimated by factors of up to 11 in the Sahara, 140 in the Canaries and 240 in Cabo Verde. In the Caribbean, there is negligible modelled contribution of d > 20 µm particles to total mass, compared to 10 % in the observations. This work adds to the growing body of research that demonstrates the need for a process-based evaluation of climate model dust simulations to identify where improvements could be implemented.